Essential attributes and qualifiers of primary health care - doi:10.5020/18061230.2012.p3 - Andréa Sílvia Walter de Aguiar; Pollyanna Martins (Universidade de Fortaleza, 2012)
Historically, the primary health care (PHC) has been associated with the first level of care from a health system and characterized by the kind of professional that in it operates, where is expected a predominance of specialists in this area. However, the major limitation for this type of characterization is that the profile of professionals engaged in this service may vary from country to country. Several theoretical and conceptual landmarks proposed approaches and indicators to assess and characterize the APS. In 1978, the American Institute of Medicine suggested an approach in which listed its attributes such as accessibility, integrality, coordination, continuity and responsibility. This was an important landmark in an attempt to outline a normative approach to measure it. However, most indicators and specific definition was not suggested. The selected indicators required a high level of performance, were difficult to be achieved, and focused on the capacity of services and not in its concrete realization(1).A 1996 report, from the same institution, defined PHC as the provision of integrated services and accessible by clinicians who are responsible for attending a large majority of personal care needs, developing a continued partnership with patients and working within family and community. This definition does not include the first contact and focuses on individual attention.The Canadian Medical Association, in 1996, considered the APS as a front door of the health system and community interventions included in the definition of the functions of APS. In the same year was published a Charter for General Practice / Family Medicine in Europe (Letter to General Practice / Family Medicinein Europe), which describes 12 characteristics: general, accessible, integrated,continuous, as a team, holistic, personalized, targeted for the family and the community, coordinated, confidential and protectress(2).Donabedian(3) systematized a group of important variables that can assess the quality of a system or health service and rated according to their characteristics in structure, process and outcome. The evaluation of the process includes the quality of services provided by health professionals individually or in groups and refer to professional qualifications, organization and coordination of the work process of teams. The evaluation of the structure includes environmental conditions and equipment in which the services are provided and the results are evaluated starting from the verification of changes in health status of a population that can be attributed to the care process. Among the theoretical and conceptual landmarks of the PHC highlights the publication "Primary Care: Balancing Health Needs, Services, and Technology", by Professor Barbara Starfield, in 1998, translated into Portuguese and published in Brazil in 2002. The book provides evidence on the role of PHC in health systems, evidence of its impact on population health, and compares the cost-effectiveness between countries with different forms and different degrees of implementation of this strategy, and propose a structure for measure it and set its attributes(1). The views of PHC, centered in the individual and in the population, provided the normative basis for evaluating it in a health system and contributed to the construction of the evaluation framework proposed by Starfield(1).The author also proposed a framework for evaluating the PHC which considered the concepts of the essential attributes and derivative measures of structure (capacity) and process (performance).The essential and exclusive attributes of the PHC include: access / care on first contact, longitudinality, integrality and coordination of care. A high level of reach of essential attributes of the PHC results in three additional aspects, denominated derivatives, which qualify the actions and services at this level of care(1,4).The aspects qualifiers are: centered on the family, cultural competence and community orientation. In most countries, nor centered on the family nor the community orientation are systems focus. The community orientation is an ideal rather than a reality(1,4).The National Primary Care Policy points out, in its guidelines, the universal and continuing access to health care quality and resolute, featuring primary care as the entry door and preferred care network. This care network should embrace users and promote linking and co-responsibility for the attention to their health needs(5). In the current issue of Brazilian Journal of Health Promotion, the reader can look into the User of the Family Health Strategy: knowledge and satisfaction with embracement, which contains important information that demonstrate mechanisms to ensure accessibility and embracement, from the comprehension of the user. Among the strategies for the development of integrality and coordinated care, now are exalted communities of practice, in which groups are formed around the practice of profession, linked from the need to share experiences so that knowledge can be collective(6). Articles "Community of practice as way of collective learning" and "Development of practices and knowledge in the Family Health Strategy: theoretical study" emphasize the learning derived from the exchange of experiences, sharing of meanings, observations, reflections on PHC.